2017
DOI: 10.1161/jaha.116.005330
|View full text |Cite
|
Sign up to set email alerts
|

An East Asian Common Variant Vinculin P.Asp841His Was Associated With Sudden Unexplained Nocturnal Death Syndrome in the Chinese Han Population

Abstract: BackgroundWe have identified the cardiomyopathy‐susceptibility gene vinculin (VCL) mutation M94I may account for a sudden unexplained nocturnal death syndrome (SUNDS) case. We addressed whether VCL common variant D841H is associated with SUNDS.Methods and ResultsIn 8 of 120 SUNDS cases, we detected an East Asian common VCL variant p.Asp841His (D841H). Comparing the H841 allele frequency of the general population in the local database (15 of 1818) with SUNDS victims (10 of 240) gives an odds ratio for SUNDS of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The H841 allele was more frequent in SUNDS and gave an odds ratio of 5.226 compared with controls. Similar to M94I, D841H also reduced peak I Na without changing the interaction or co‐localization …”
Section: Vinculinmentioning
confidence: 75%
See 2 more Smart Citations
“…The H841 allele was more frequent in SUNDS and gave an odds ratio of 5.226 compared with controls. Similar to M94I, D841H also reduced peak I Na without changing the interaction or co‐localization …”
Section: Vinculinmentioning
confidence: 75%
“…However, electrical study showed that SCN5A ‐ H558R not only reversed the decrease of peak I Na amplitude caused by VCL‐D841H , but also significantly increased the late I Na for VCL ‐ D841H in HEK293 cells. In addition, SCN5A ‐ H558R and VCL ‐ D841H were detected in 1 SUNDS case . These suggest that compound variants might play a critical role in SUNDS.…”
Section: Vinculinmentioning
confidence: 87%
See 1 more Smart Citation
“…There are several techniques for DNA mutation analysis, such as direct Sanger sequencing or next‐generation sequencing . The SNaPshot multiplex technique in our study is a minisequencing method for SNP detection in molecular genetic testing, which can be easily applied in the laboratory workflow.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic background of SCD has been addressed in recent years. In forensic medicine, SCD‐related mutations are screened using next‐generation sequencing and whole‐exome sequencing techniques . However, these methods are too expensive for most laboratories and it is hard to meet the demand for examinations, given the worldwide SCD epidemic.…”
Section: Introductionmentioning
confidence: 99%